Penyuluhan Digitalisasi Pemasaran Produk UMKM Kemplang Ubi di Desa Talang Nangka, Kab. Muara Enim, Kec. Lembak - Pera Dwiwansi; Dewi Puspita Rahayu; Chairunnisa Chairunnisa; Tegar Try Anugrah; M. Andrian Rizki Nugraha; Meilin Veronica; Muhammad Bahrul Ulum; Rum Hendarmin (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
MSME stands for Micro, Small and Medium Enterprises. In its implementation, MSMEs apply the principles of togetherness, a democratic economy, independence, balance of progress, sustainability, efficiency of justice, and national economic unity. In Indonesia, National MSME Day is celebrated every March 31. MSMEs are people's businesses that currently receive attention and privileges mandated by law, including business credit assistance with low interest, ease of business license requirements, business development assistance from government agencies, and several other facilities.The government supports Indonesian citizens to run micro and small businesses, especially in Talang Nangka Village, Kec. Lembak. They want to be able to penetrate the halal market and carry out a trade process in the local market to introduce their products. The implementation problem that occurs is that the training is uneven in depth, for example in Talang Nangka Village there are several business actors who do not understand how to cope in the era of digitalization. For example, trade in the digitalization era can use E-Commerce, websites, Instagram businesses, whatsapp business and others. So that the 2022 Real Work Lecture program can help business actors to better understand technology and be able to sell easily, because based on the research obtained, business actors currently only get income from selling products to neighbors and the holiday market.